The THE INFLUENCE OF TAXPAYER AWARENESS, TAX SOCIALIZATION AND PUBLIC SERVICE ACCOUNTABILITY ON MOTOR VEHICLE TAXPAYER COMPLIANCE (Case Study at SAMSAT Office, North Jakarta): PENGARUH KESADARAN WAJIB PAJAK, SOSIALISASI PAJAK DAN AKUNTABILITAS PELAYANAN PUBLIK TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR (Studi Kasus di Kantor SAMSAT Kota Jakarta Utara) - Suryani; Julian Muhammad Hasan (Shofanah Media Berkah, 2022)
This study aims to examine the effect of taxpayer awareness, tax socialization, and public service accountability on motor vehicle taxpayer compliance at the North Jakarta City Samsat Office. The method of determining the sample using random sampling. The data used is primary data collected through a questionnaire. The questionnaires that were processed were 100 questionnaires. And analyzed using SPSS version 26 with validity and reliability test methods, regression analysis, R2 test, f test and t test. This study uses multiple linear regression analysis to test the hypothesis. The results showed that taxpayer awareness, tax socialization, and public service accountability at the North Jakarta City Samsat Office were categorized as good. The results of partial hypothesis testing prove that taxpayer awareness, tax socialization, and public service accountability have an effect on motor vehicle taxpayer compliance. Simultaneously, taxpayer awareness, tax socialization, and public service accountability have a significant effect on motor vehicle taxpayer compliance at the North Jakarta City Samsat Office